Contributions to the natural history of Mormopterus kalinowskii (Chiroptera: Molossidae) in the southwest of Peru - Flores-Quispe, Marisel; Calizaya-Mamani, Giüseppy; Portugal-Zegarra, Gandhy; Aragon Alvarado, Giovanni; Pacheco-Castillo, Jaime; Rengifo, Edgardo M. (THERYA, 2019)
Mormopterus kalinowskii, is an insectivorous species restricted to the Andean western slopes of Peru and Chile, it is rare and has very scarce available information. We evaluated sex ratio, roost use, and relationship between reproductive patterns and monthly seasonal variation throughout a 13-month period. In addition, we performed the first description and characterization of its echolocation calls. The study area was located in the Ite Valley, Tacna department (southwestern Peru) at the northernmost part of the Atacama Desert, one of the driest deserts in the world. Bats were caught using mist-nets. Sex ratio in the population was calculated from all individuals captured, and its difference with regard to a 1:1 ratio was assessed through a Binomial Coefficient Test. Roost use was assessed through observation and inspection of the study area. Pearson and Spearman correlation coefficients were calculated to establish the relationship between the number of captures and temperature and precipitation data. Echolocation calls were recorded using a Petterson D240x Ultrasound detector plugged to a digital recorder. Spectrogram displays of recorded calls allowed describing structural patterns within echolocation calls and to measure frequency and time parameters. 79 individuals of M. kalinowskii were captured; 30 males and 49 females. Sex ratio obtained, 1:1.63, evidenced more females in the study area. M. kalinowskii uses crevices as roosts and has a single reproductive cycle per year. Higher capture rates are correlated with temperature (r = 0.526), but not precipitation (r = 0.096). Calls in search phase exhibited long duration pulses and a descending quasi-constant frequency (QCF) component from 39 to 33 kHz, reducing length and increasing bandwidth when attempting to catch prey. The sex ratio, 1:1.63 (â‰ˆ 2), suggests that M. kalinowskii is a polygamous species, as occurs in the others molossids, whereas the single annual reproductive cycle shown by M. kalinowskii would indicate a seasonal monoestrous reproductive pattern. Echolocation calls share several traits observed in other molossids; however, the frequency values for M. kalinowskii search phase pulses could be the highest recorded among the molossid bats of the Pacific coastal desert, allowing them to detect smaller prey as a strategy to mitigate food competition among insectivorous bats in arid environments.